Enfermedad de inclusión citomegálica. - Duyos Gato, Héctor; Pelayo González Posada, Eduardo; Almanza Más, Manuel; Cabrera Arregoitia, Jesús (Revista Cubana de Pediatría, 2023)
Describe las formas de infección de esta entidad.